Determination of binding constants of multiple charged cyclodextrin complexes by ACE using uncorrected and ionic strength corrected actual mobilities of the species involved - Sázelová, Petra; Koval, Dušan; Severa, Lukáš; Teplý, Filip; Vigh, Gyula; Kašička, Václav (Electrophoresis, 2020)
In this study, the apparent binding constants and limiting mobilities of the multiply charged complexes of the Δ- and Λ-enantiomers of Ru(II)- and Fe(II)-polypyridyl associates ([Ru(2,2'-bipyridine)3 ]2+ , [Ru(1,10-phenanthroline)3 ]2+ , and [Fe(1,10-phenanthroline)3 ]2+ ) with single-isomer 2,3-diacetylated-6-sulfated-cyclodextrins (CDs) (12Ac-6S-α-CD, 14Ac-7S-β-CD, and 16Ac-8S-γ-CD) were determined by ACE using uncorrected and ionic strength corrected actual mobilities of the species involved. Two limiting models were tested for the ionic strength correction of the actual mobilities based on an empirical relation for the ionic strength correction of multivalent ionic species. In model 1, the nominal values of the charge numbers (zS,nom ) and analytical concentrations (cS,nom ) of the above CD selectors in the BGEs were applied for calculation of the BGE ionic strength, as usual. In model 2, the CD selectors were considered as singly charged species (zS = -1) with |zS,nom |-times higher concentrations in the BGE than their analytical concentrations (cS = |zS,nom | × cS,nom ) in the calculation of the BGE ionic strength. In all three cases-with uncorrected actual mobilities as well as with actual mobilities corrected according to the two limiting models-the measured effective mobilities of the above enantiomers fit well the theoretical curves of their mobility dependences on the CD selectors concentrations in the BGE, with high average coefficients of determination (R2 = 0.9890-0.9995). Nevertheless, the best physico-chemically meaningful values of the apparent binding constants and the limiting mobilities of the enantiomer-CDs complexes with low RSDs were obtained using the actual mobilities of the species involved corrected according to model 2.
Keywords: Sulfates; Models, Molecular; cyklodextriny; sírany; Electrophoretic mobility; Binding constant; osmolární koncentrace; molekulární modely; Osmolar Concentration; Electrophoresis, Capillary; Affinity capillary electrophoresis; Ionic strength; Stereoisomerism; stereoizomerie; elektroforéza kapilární; Cyclodextrins